Futures Trading, Spot Price Volatility and Structural Breaks: Evidence from Energy Sector - Shirodkar, Sanjeeta; Raju, Guntur Anjana (International Journal of Energy Economics and Policy, 2021)
The present study empirically examines the impact of Stock Futures on India’s underlying Energy Sector Stocks by incorporating the Structural breaks in the AR (1)-GARCH (1, 1) model. Although the issues relating to the effect of Derivatives trading on Cash Market Volatility have been empirically discussed in two ways: by evaluating Cash Market Volatilities during the Pre-and Post-Derivatives trading periods and, secondly, by determining the influence of Derivatives trading on the conduct of Cash Markets by comparing it with proxies. Nevertheless, these methodologies cannot isolate the influence of derivatives trading from the effects of other market reforms on the volatility of the underlying Cash Market. The study offers mixed results for the select sample of Energy sector stocks. However, there is evidence of a reduction in unconditional volatility for most energy sector stocks. The study’s findings suggest that trading in Stock Futures may not necessarily be associated with the destabilization of the underlying Energy sector Stocks. Keywords: Stock Futures; Volatility modelling; ICSS test; AR (1)-GARCH (1, 1), Structural Breaks, Futures trading, Energy Sector JEL Classifications: G11, G14 DOI: https://doi.org/10.32479/ijeep.11086